2010
DOI: 10.1097/icl.0b013e3181db352f
|View full text |Cite
|
Sign up to set email alerts
|

Improved Signs, Symptoms, and Quality of Life Associated With Dry Eye Syndrome: Hydroxypropyl Cellulose Ophthalmic Insert Patient Registry

Abstract: Hydroxypropyl cellulose ophthalmic inserts significantly improved signs and symptoms of moderate-to-severe DES, as well as ADL and QoL. Benefits were additive to those seen with patients' existing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…23 Schiffman et al 23 recommended the use of OSDI as an endpoint in clinical trials. Several recent studies of dry eye syndrome 30-32 and 1 study of ocular GVHD 33 used changes in OSDI as an endpoint. Our results showed that changes in OSDI correlated with clinician- and patient-reported symptom changes in ocular GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…23 Schiffman et al 23 recommended the use of OSDI as an endpoint in clinical trials. Several recent studies of dry eye syndrome 30-32 and 1 study of ocular GVHD 33 used changes in OSDI as an endpoint. Our results showed that changes in OSDI correlated with clinician- and patient-reported symptom changes in ocular GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Because the formulation is preservative free, it may help patients who are not able or willing to use artificial tears on a frequent basis [96,97]. Published clinical evidence of efficacy (level II) has reported a significant improvement in tear deficiency symptoms and OSDI scores with once-daily use of hydroxypropyl cellulose ophthalmic inserts [98,99]. Transient blurred vision was the most common adverse event reported that was associated with use of the hydroxypropyl cellulose ophthalmic inserts [97,98].…”
Section: Treatment Options For Dysfunctional Tear Syndromementioning
confidence: 99%
“…Dry eye is a multifactorial ocular surface disorder which is usually caused by chronic inflammation and characterized by tear film instability and increased osmolarity [1, 2]. There are various symptoms in dry eye patients, such as ocular discomfort, fluctuating visual disturbances, and potential damage [3].…”
Section: Introductionmentioning
confidence: 99%